2007
DOI: 10.1094/phyto-97-0051
|View full text |Cite
|
Sign up to set email alerts
|

Symptom Remission and Specific Resistance of Pepper Plants After Infection by Pepper golden mosaic virus

Abstract: Pepper golden mosaic virus (PepGMV) is an important begomovirus infecting solanaceous crops in Mexico and Central America. Under controlled conditions for growth and inoculation with a low-pressure biolistic device, PepGMV-infected pepper plants consistently showed symptom remission or host recovery 12 to 15 days postinoculation (dpi). Inoculated plants initially developed the characteristic PepGMV symptoms; however, newer leaves presented a significant decrease or disappearance of symptoms. Younger asymptomat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
57
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 50 publications
10
57
0
Order By: Relevance
“…5B). The recovery phenotype in plants infected with begomoviruses is a type of defense response and is associated with reduced levels of viral DNA (55,56). Results of DNA gel blot hybridization analyses indicated that viral DNA levels were similar and relatively high for all three genotypes at 21 dpi, when infected plants showed severe leaf curl symptoms (Fig.…”
Section: Toldev Is Associated With Tolcd In Peru Andmentioning
confidence: 95%
“…5B). The recovery phenotype in plants infected with begomoviruses is a type of defense response and is associated with reduced levels of viral DNA (55,56). Results of DNA gel blot hybridization analyses indicated that viral DNA levels were similar and relatively high for all three genotypes at 21 dpi, when infected plants showed severe leaf curl symptoms (Fig.…”
Section: Toldev Is Associated With Tolcd In Peru Andmentioning
confidence: 95%
“…Sonora Anaheim) seeds were germinated in a bioclimatic chamber at 26 to 28°C with a 16/8-h (light/dark) photoperiod. The fourth leaf on plants at the four-leaf stage (around 30 days postgermination) were inoculated with PepGMV (pepper golden mosaic virus) infectious dimeric clones or with pBluescript for mock inoculations by biolistic bombardment (20). Samples of symptomatic tissue were harvested 10 days postinoculation (dpi), whereas recovered tissue was harvested at 24 dpi.…”
Section: Methodsmentioning
confidence: 99%
“…Previous results have suggested that viral minichromosomes from symptomatic and recovered tissues could present differences in structure organization (19,20). Therefore, we decided to compare the minichromosome populations from both types of tissue using a micrococcal nuclease sensitivity assay.…”
Section: Micrococcal Analysis Of Viral Minichromosomes From Symptomatmentioning
confidence: 99%
See 2 more Smart Citations